Supporting activity engagement by family carers at home: maintenance of agency and personhood in dementia. Issue 1 (1st January 2017) - Chung, Pat Yin Fan; Ellis-Hill, Caroline; Coleman, Peter
ABSTRACT: An explorative paper to describe how family carers, through the caregiving journey, reaffirm and promote the agency of people with dementia. Agency is an important concept in dementia care and is crucial to the promotion of wellbeing and the delivery of person-centred care. This article is based on one of the key findings of a study that explored family carers' experiences of engaging their relatives in daily activities in domestic settings. Following research governance and ethical approval, 30 in-depth interviews (initial and follow-up) were carried out with 15 resident-carers of people with dementia who were recruited via local community mental health teams. Then five focus groups were conducted with 21 participants accessed through carers support groups. Interviews and focus groups were transcribed, coded and analysed using a grounded theory method. Findings showed the process in which family carers encouraged and sustained a sense of autonomy and control (agency) in their relative's daily activities. Key strategies used by carers included: being non-judgemental; facilitating a sense of worth; taking calculated risks; maintaining the continuity of their relative's identity; enhancing a sense of connection with their relative's role and identity using enjoyable activities; preventing inactivity and attending to the bodily source of the agency. Lack of support for carers could ultimately pose a risk to the maintenance of the agency of people with dementia. This study provides a deeper insight into the process used by home carers to support the agency of people with dementia. This is essential if practitioners are to identify and develop more realistic intervention strategies and to work in effective partnership with family carers. The implications for the creation of dementia-friendly communities are discussed.